Reach Space Analysis of Baseline Differential Extrinsic Plasticity Control - Birrell, Simon; Abdulali, Arsen; Iida, Fumiya (Frontiers in Neurorobotics, 2022)
The neuroplasticity rule Differential Extrinsic Plasticty (DEP) has been studied in the context of goal-free simulated agents, producing realistic-looking, environmentally-aware behaviours, but no successful control mechanism has yet been implemented for intentional behaviour. The goal of this paper is to determine if ”short-circuited DEP”, a simpler, open-loop variant can generate desired trajectories in a robot arm. DEP dynamics, both transient and limit cycles are poorly understood. Experiments were performed to elucidate these dynamics and test the ability of a robot to leverage these dynamics for target reaching and circular motions.